ANALYSIS OF CHANGES IN TRANSPORT PROCESSES IN WARSAW PUBLIC TRANSPORT IN THE FACE OF DISRUPTIONS IN 2019-2022 - Andrzej ŚWIDERSKI; Sebastian SOBCZUK; Anna BORUCKA (Scientific Journal of Silesian University of Technology. Series Transport)
Public transport focuses on meeting the transport needs of people both within the city and in the suburban area. Passenger transport is a key element of sustainable development and improving the quality of life in agglomerations because it provides mobility for residents and tourists. In recent years, residents have become increasingly willing to use public transport. However, this trend was disrupted as a result of global changes taking place in the years 2019 - 2022. The aim of this publication was to analyse and assess the impact of crisis situations on the implementation of transport processes using the example of public transport in Warsaw. It has been shown that events such as the COVID-19 pandemic or the war in Ukraine also had a significant impact on the functioning of transport processes in Warsaw public transport. The study made it possible to identify recommendations aimed at securing the operation of public transport in the event of similar threats in the future.